FOSS4G 2013 Academic Papers : FOSS4G2013 Proceedings of OSGeo Journal, Nottingham (UK), from 17 to 21 September 2013 (OSGeo, 2020)
This issue of the OSGeo Journal, comprising twelve research papers selected from the submissions to the Academic Track of FOSS4G 2013, the global conference for Open Source Geospatial Software, which took place in Nottingham (UK), from 17 to 21 September 2013. FOSS4G is not an academic conference. The core audience has always been the people who make up the open source communities: The people that develop, create and craft the open source geo-spatial software. The actual applications are the glue which binds the community together; the aim of the FOSS4G community is to enable and enfranchise anyone to harness the power of geo-spatial software, regardless of their economic status. To acknowledge this, and to not create an isolated, exclusive, part of the conference, we scheduled presentations of the papers clustered with other, non-academic, papers based on subject matter. By this, we hope to have generated attention for academic input in the community and to cross-pollenate with industry, developers and users.